Oral mucosal lesions - A study of 369 cases - Varun R Jain; Rashmi S Mahajan; Shreya S Rathi; Vinaykumar V Biyani; Kishan R Ninama; Yogesh S Marfatia (Wolters Kluwer Medknow Publications, 2023)
Background: Diagnosing and treating oral cavity lesions is a challenging task for most of the clinicians due to similar symptoms and clinical appearances. Frequently, histopathology and immunohistochemistry aid in making the diagnosis. Objectives: The objectives were to describe the clinical features, and histopathological features and systemic association in patients with oral mucosal lesions (OML). Materials and Methods: A cross-sectional descriptive study was undertaken at a tertiary care centre in patients with OML. A total of 369 cases with OML were included in the study. Results: Males constituted 61.78% of the cases. History of habits such as tobacco, gutka chewing, smoking, and alcohol was given by 32.25%, 29.81%, 26.56%, and 11.38% of cases, respectively. Common symptoms were soreness, burning sensation, oral pain and ulcers. Both oral and cutaneous involvement was seen in 17.89% of cases. Oral lichen planus (oral LP) constituted largest group of patients (21.96%) wherein reticulate type was the most frequent type and buccal mucosa was the commonest site. Oral carcinomas constituted 20.33% of cases followed by infective etiology (11.92%), vesiculobullous group of diseases (10.30%), aphthous stomatitis (8.94%), premalignant lesions (7.05%) such as leukoplakia (3.80%) and submucous fibrosis (2.44%). Histopathology was done in 209 cases. Clinico-histopathological correlation was seen in oral LP (90.27%), oral pemphigus (82.35%), and malignancies (98.66%). Conclusion: Oral LP formed the largest group of cases followed by Oral squamous cell carcinoma (SCC). Several rare conditions, such as Melkersson-Rosenthal syndrome and blue rubber bleb nevus syndrome were also a part of the study. Thorough clinical and histopathological examination in this diverse group of diseases clinches the diagnosis.